A vector radiative transfer model for simulating the microwave emissivity of sea foam based on matrix operator method - Jin, Xuchen; He, Xianqiang; Bai, Yan; Wang, Difeng; Ying, Jianyun; Zhu, Qiankun; Gong, Fang; Zhou, Chenghu; Pan, Delu (Frontiers in Marine Science, 2023)
Modeling sea foam emissivity is important for microwave remote sensing of the ocean. Based on the matrix-operator method, we propose a vector radiative transfer model (RTM) for the simulation of wave propagation in the foam layer and the sea foam emissivity is then calculated. The RTM simulates the emissivity of a vertically structured foam layer with various water properties. We assess the model simulations under different conditions. It is found that the foam thickness and the void fraction profile could be critical parameters in modeling foam emissivity. The sea foam emissivity could range from 0.2 to 0.3 in our simulations with varying foam thicknesses and void fraction profiles. Then, comparisons were made to experimental data for validation, and our model achieved a good consistency with the different experimental measurements of three previous studies. And it was also found that the modeled emissivity fits the experimental data well using an exponential profile with a small profile shape-control parameter.